A cuticular protein essential for sperm dimorphism and male fertility in Bombyx mori - Zhongwei Li; Bing Zhang; Chenyue Zhao; Yanyan Wang; Ruoke Wang; Camilo Ayra-Pardo; Yunchao Kan; Dandan Li (Insect Biochemistry and Molecular Biology, 2026)

A novel ionic liquids phase change absorption system for carbon dioxide capture and utilization - Yuqing Chang; Yujiao Wu; Ruoke Liu; Yuan Jiang; Zhijun Zhou; Tianlin Wang; Xiaochun Chen (Fuel, 2024)

Study on Fatigue Spectrum Analysis and Reliability Analysis of Multilayer Flexible Riser - Jianxing Yu; Fucheng Wang; Yang Yu; Haoda Li; Xin Liu; Ruoke Sun (Journal of Marine Science and Engineering, 2022)
Multilayer composite flexible risers have been widely used in engineering. However, this type of structure is complex, as there are influences between layers. Moreover, a range of uncertain factors need to be considered in fatigue analysis. Therefore, it is difficult to perform the fatigue analysis research of multilayer flexible risers. In this paper, the fatigue spectrum analysis and reliability analysis method of a nine-layer flexible riser structure are proposed, and a complete fatigue and reliability analysis process for multilayer structures is developed. The theoretical basis of the fatigue spectrum analysis method is introduced, and the calculation program is described. Finite element software is used to analyze the stress of the multilayer flexible riser under the influence of the upper platform structure movement and the ocean current. Moreover, the stress response of the riser structure of each layer is obtained. According to this, the irregular wave load is simulated by the method of random number simulation, and the stress response spectrum is formed. Then, the appropriate S-N curve is selected to calculate the fatigue damage degree of each layer, and the fatigue damage nephogram is displayed, so as to analyze the structural fatigue damage. Finally, the uncertainty in the process of fatigue damage calculation is analyzed. According to the results, the methods of multilayer riser analysis are summarized and the future research directions are put forward.